Assessment of lipid oxidation in Atlantic mackerel (Scomber scombrus) subjected to different antioxidant and sous-vide cooking treatments by conventional and fluorescence microscopy methods. (October 2019) - Cropotova, Janna; Mozuraityte, Revilija; Standal, Inger Beate; Rustad, Turid
Abstract: The aim of this study was to assess lipid oxidation development in sous-vide cooked Atlantic mackerel during chilled storage by fluorescence microscopy coupled with chemical, physical and data analysis methods. Sous vide-cooking at 70 °C and 80 °C for 10 and 20 min was performed with and without use of antioxidants. Fluorescence micrographs of lipids extracted from the fish samples on 1st, 3rd, 7th, and 9th day of chilled storage at 4 ± 1 °C, were acquired in the wavelength region of λex 475/40 and λem 530/50 (44 FITC filter). The obtained images were numerically processed and the resulting data correlated with 2-thiobarbituric acid reactive substances (TBARS) determined by conventional chemical method of lipid oxidation analyses. Total lipid content and color characteristics of mackerel fillets were analyzed as well. The yellowness of the fish flesh significantly correlated (p < 0.05, R = 0.859) with conjugated trienes generated from thermal polymerization of lipids during chilled storage of sous-vide cooked mackerel. Results showed that higher temperature and cooking times generally accelerated lipid oxidation in mackerel samples prepared both with and without addition of antioxidants in terms of conjugated trienes and tetraenes. However, the addition of antioxidants enhanced the lipid oxidation stability of cooked mackerel fillets. Highlights: Fluorescence correlated with 2-thiobarbituric acid reactive substances. Yellowness of the fish flesh correlated with conjugated tetraenes. Conjugated structures increased with increased cooking temperature and time. Antioxidants enhanced lipid oxidation stability of cooked mackerel fillets.